Linking Deep Earth and Surface Processes. (29th January 2013) - Cloetingh, Sierd; Willett, Sean D.
Abstract : One of the important developments in Earth science over the past decade has been recognition of the significance of linking deep Earth dynamic processes with surface and near‐surface geologic processes [e.g., Braun, 2010]. Deep Earth research, encompassing fields such as seismology and mantle geodynamics, has traditionally operated distinctly from fields focusing on dynamics of the Earth's surface, such as sedimentology and geomorphology. However, these endeavors have in common the study of Earth's topography and the prediction of changes in its surface. Observables from surface studies, such as basin stratigraphy, geomorphology of landscapes, changes in surface elevation, and changes in sea level, provide some of the principal constraints on geodynamic and tectonic models. Conversely, deep geodynamic processes give rise to the topography, erosion, and sediment generation that are the basis of surface geology. Surface manifestations of deep geodynamic processes have significant societal impact by creating natural hazards, such as earthquakes and mass movements, and controlling the distribution of natural resources such as fossil fuels or geothermal energy. The relevance of research conducted in both the deep Earth and surface regimes is thus enhanced through a focus on their interaction.